Closing the waste loop by thermochemical conversion of municipal solid waste : an analytical study - Tan, Jun Jie (2019)
At present, the treatment of municipal solid waste (MSW) by landfill and incineration approaches pose its issues, therefore new alternative solutions such as advanced thermochemical processes which include pyrolysis, gasification and hydrothermal treatment are attracting great interests. However, to maximise the efficiency of these systems, the composition of the MSW and its reactions under different heating conditions and rates have to be well understood. Thermogravimetric analysis (TGA) was used to analyse the thermal decomposition of various wastes typically present in MSW, namely food, horticultural, paper, plastic, textile and wood wastes. These data are then cross-referenced with existing literature to understand the composition and properties of these wastes individually. These data are then compared to the refuse derived fuel (RDF) pellet made based on the statistically determined composition of MSW, through the use of kinetics analysis, such as model fitting kinetics, Friedman analysis and Ozawa-Flynn-Wall analysis. Results suggest that the combined kinetics of individual wastes sync well with the kinetics of the RDF pellet, suggesting significant potential for further research into the composition of MSW to improve the understanding of the behaviours of thermochemical conversion of wastes.